Deep Peroneal Nerve Palsy Caused by an Extraneural Ganglion Cyst: A Rare Case - Dimitrios Nikolopoulos; George Safos; Neoptolemos Sergides; Petros Safos (Case Reports in Orthopedics)
Lower extremities peripheral neuropathies caused by ganglion cysts are rare. The most frequent location of occurrence is the common peroneal nerve and its branches, at the level of the fibular neck. We report the case of a 57-year-old patient admitted with foot drop, due to an extraneural ganglion of the upper tibiofibular syndesmosis, compressing the deep branch of the peroneal nerve. Although there have been many previous reports of intraneural ganglion involvement with the lower limb nerves, to our knowledge, this is the second reported occurrence of an extraneural ganglion distinctly localized to the upper tibiofibular syndesmosis and palsying deep peroneal nerve. The diagnosis was made preoperatively using MRI. The common peroneal nerve and its branches were recognized and traced to its bifurcation during the operation, and the ganglion cyst was removed. Two months after surgery, the patient was pain-free and asymptomatic except for cutaneous anesthesia in the distribution of the deep peroneal nerve.